Find solutions to your problems with the help of IDNLearn.com's knowledgeable users. Ask any question and get a thorough, accurate answer from our community of experienced professionals.
Transformation involves changing the form of a function. The function that represents is C; [tex]g(x) =- \sqrt[3]{x+1}[/tex]
The function is a type of relation, or rule, that maps one input to specific single output.
Function f(x) is given byy;
[tex]g(x) = \sqrt[3]{x}[/tex]
f(x) is reflected across the x-axis.
The rule of this transformation (i.e. reflection) is:
(x, y) ⇒ (x, - y)
So,
[tex]f'(x) = -f(x)[/tex]
This gives
[tex]f'(x) = - \sqrt[3]{x}[/tex]
Now, f'(x) is translated 1 unit left
The rule of this transformation (i.e. translation) is:
(x, y) ⇒ (x+ 1, y)
So,
g(x) = f'(x+ 1)
This gives
[tex]g(x) = -\sqrt[3]{x+1}[/tex]
Hence, the function that represents g(x) is (c)
Learn more about function here:
https://brainly.com/question/2253924
#SPJ1